Aspectos hidrogeológicos da microbacia do rio Maguariaçú: uma proposta alternativa de abastecimento de água para área Central do município de Ananindeua-PA - PANTOJA JÚNIOR, Antonio Francisco Pinheiro (2019)
With an area of 191 km2 and a population of 471,744 inhabitants the municipal district of Ananindeua has a population density of 2.470 inhab/km2 (IBGE Cities, 2010). This catchment area has a strong urban occupation. Among these industries, shopping centers, gas stations, recreational club, supermarkets, bus garages, residential development and a population density that is growing every year. The human activities in the region have contributed significantly to the degradation of natural resources, especially water bodies, while they have a supply network not to fulfil the demand. The survey was conducted in Maguariaçu River Basin, belonging to the limits of the the municipality of in Ananindeua mesoregion metropolitan Belém. However, the study focused only on the region nascent of the basin (microbasin). The aim of this work aims to study the behavior of underground water flow and analyze water quality in River Microbasin Maguariaçu(MRM), and from these data, identify areas of recharge to the aquifer top, knowing the geometrical characteristics of theunderground water flow identify contaminants, perform the calculation of reserves of the aquifer and to develop proposedwater supply for the area of MRM, Ananindeua-PA.